Addition of MCP-1 and MIP-3β to the IL-8 appraisal in peritoneal fluid enhances the probability of identifying women with endometriosis. (June 2015) - Borrelli, G.M.; Kaufmann, A.M.; Abrão, M.S.; Mechsner, S.
Highlights: Several chemokines have been tested for endometriosis so far. For the first time the systematically selected chemokines were evaluated together in a multiplexed assay. IL-8, MCP-1, and MIP-3β had statistically significant higher concentrations in the PF of women with endometriosis. The combined assessment of MCP-1, MIP-3β, and IL-8 improved the likelihood of identifying patients with endometriosis. Abstract: Chemokines have been associated with endometriosis. Our study was aimed at evaluating the levels of six chemokines – CXCL8 (IL-8), CXCL12 (SDF-1), CCL2 (MCP-1), CCL5 (RANTES), CCL19 (MIP-3β), and CCL21 (6-Ckine) – in the peritoneal fluid (PF) of patients with and controls without endometriosis by multiplexed cytokine assay. In this retrospective case–control study conducted at the Charité University Hospital, patients ( n  = 36) and controls ( n  = 27) were enrolled. The patients were separated into groups according to stage of the disease: I–II ( n  = 21), III–IV ( n  = 15), and according to clinical findings: peritoneal endometriosis (PE; n  = 7), deep-infiltrating endometriosis (DIE) affecting the retrocervical area ( n  = 13) or the bowel/rectovaginal site ( n  = 14). The subjects were also separated according to the cycle phase: follicular ( n  = 14) or luteal ( n  = 8) and the previous use ( n  = 25) or not ( n  = 38) of hormones. PF was collected from all subjects ( n  = 63) consecutively during laparoscopy. The concentration of chemokines in the PF was assessed using Luminex ® x-MAP ® technology. Sensitivity and specificity were calculated. A model of multiple logistic regressions estimated the odds of endometriosis for each combination of the chemokines detected. We observed significantly higher concentrations of IL-8 ( p  < 0.001), MCP-1 ( p  = 0.014), and MIP-3β ( p  = 0.022) in the PF of women with endometriosis than in the controls. A joint evaluation revealed that elevated levels of the three chemokines had a positive endometriosis prediction value of 89.1%. The combined assessment of MCP-1, MIP-3β, and IL-8 concentration in PF improved the likelihood of identifying patients with endometriosis. Future studies should investigate this panel in peripheral blood samples.